Short-Run and Long-Run Elasticities for Canadian Consumption of Alcoholic Beverages: an Error-Correction Mechanism/Cointegration Approach - Johnson, James A.; Oksanen, Ernest H.; Veall, Michael R.; Fretz, Deborah (The Review of Economics and Statistics, 1992)
Elasticities for beer, wine and spirits are estimated for each of the provinces of Canada over the period 1956-83, using unrestricted dynamic regressions modeled after the error-correction mechanism. Alternative long-run estimates are also obtained from cointegrating regressions. Estimates vary markedly across provinces and suggest that increases in price will reduce consumption of all beverages in the short run, but in the long run no evidence is found that spirits use is price-sensitive. Increases in the legal drinking age reduce consumption in the short run but there is little indication of a long-run effect. The estimated income elasticity of beer is small while the estimated income elasticities for spirits and wine are substantially larger, especially in the long run. Coauthors are Ernest H. Oksanen, Michael R. Veall, and Deborah Fretz. Copyright 1992 by MIT Press.